Spatiotemporal Pattern of Human Cortical and Subcortical Activity during Early-Stage Odor Processing - Stadlbauer, Andreas; Kaltenhauser, Martin; Buchfelder, Michael; Brandner, Sebastian; Neuhuber, Winfried; Renner, Bertold (Chemical Senses, 2016)
The dynamics of early-stage cortical and subcortical responses in the human brain to odor stimulation are currently unknown. The objective of the present study was to analyze spatiotemporal patterns of human brain activity during odor perception using magnetoencephalography (MEG). In 12 normosmic healthy subjects, we investigated the onset of brain activity in relation to ipsilateral and contralateral stimulation with 2 odorants. Olfactory stimuli (200ms duration) were applied using an olfactometer, and brain activity was recorded with a 248-magnetometer whole-head MEG system. Olfactory responses were identified shortly (within 150ms) after stimulus onset in both hemispheres. Stimulation on the ipsilateral side yielded signals earlier (starting at 90ms) compared with contralateral stimulation in the primary olfactory cortex, hippocampus, parahippocampal gyrus, amygdala, and orbitofrontal cortex (P < 0.001). The duration and peak amplitude of olfactory evoked magnetic fields were found to increase with increasing poststimulus time in the majority of the investigated cortical structures (P ≤ 0.019 and P ≤ 0.021). The study showed the locations of early olfactory brain activity in humans within 150ms after the onset of stimuli. Olfactory activation is processed on the ipsilateral side of stimulation in early stages. After a short delay of 34ms a corresponding pattern of activation was also seen in the contralateral hemisphere, indicating the functional connectivity between the 2 hemispheres in the anterior commissure.
EVALuna2:32855